Integrasi Asas Psikologi dalam Pengembangan Kurikulum Pendidikan Agama Islam - Sihono, Sihono; Hamami, Tasman (UIR Press, 2025)
The development of Islamic Religious Education curriculum in Indonesia increasingly emphasizes the integration of psychological principles to address the mental, emotional, and social needs of students. This approach aims to create a balanced learning experience that not only imparts knowledge but also fosters holistic character development. Research reveals that an academically focused curriculum often neglects students' psychological well-being, leading to decreased motivation and limited character formation. This research uses the literature study method by analysing various literatures related to developmental psychology, learning psychology, and the humanistic approach in education. Findings from this study highlight three key results: first, the relevance of psychological principles in bridging cognitive and emotional aspects of education; second, the practical strategies for embedding psychological frameworks into curriculum design to encourage student engagement and empathy; and third, the measurable impact on students’ moral development and interpersonal skills. Through a responsive curriculum aligned with Indonesia's educational goals, educators can foster an environment conducive to the intellectual, moral, and emotional growth of students. Therefore, through a qualitative literature study, this article provides conceptual insights and recommendations for the implementation of a psychologically enriched curriculum framework in Islamic Religious Education.